Cross-modal tactile–taste interactions in food evaluations. (29th July 2016) - Slocombe, B.G.; Carmichael, D.A.; Simner, J.
Abstract: Detecting the taste components within a flavoured substance relies on exposing chemoreceptors within the mouth to the chemical components of ingested food. In our paper, we show that the evaluation of taste components can also be influenced by the tactile quality of the food. We first discuss how multisensory factors might influence taste, flavour and smell for both typical and atypical (synaesthetic) populations and we then present two empirical studies showing tactile–taste interactions in the general population. We asked a group of non-synaesthetic adults to evaluate the taste components of flavoured food substances, whilst we presented simultaneous cross-sensory visuo-tactile cues within the eating environment. Specifically, we presented foodstuffs between subjects that were otherwise identical but had a rough versus smooth surface, or were served on a rough versus smooth serving-plate. We found no effect of the serving-plate, but we found the rough/smoothness of the foodstuff itself significantly influenced perception: food was rated as significantly more sour if it had a rough (versus smooth) surface. In modifying taste perception via ostensibly unrelated dimensions, we demonstrate that the detection of tastes within flavours may be influenced by higher level cross-sensory cues. Finally, we suggest that the direction of our cross-sensory associations may speak to the types of hedonic mapping found both in normal multisensory integration, and in the unusual condition of synaesthesia. Highlights: We evaluated tactile–taste interactions in the general population. Food was rated as significantly more sour if it had a rough (versus smooth) surface. Perceived intensity of taste may be influenced by higher level, cross-sensory cues.